2021
DOI: 10.21425/f5fbg51146
|View full text |Cite
|
Sign up to set email alerts
|

Climatic drivers of Sphagnum species distributions

Abstract: Peat mosses (genus Sphagnum) dominate most Northern mires and show distinct distributional limits in Europe despite having efficient dispersal and few dispersal barriers. This pattern indicates that Sphagnum species distributions are strongly linked to climate. Sphagnum-dominated mires have been the largest terrestrial carbon sinks in Europe over the last few millennia. Understanding the climatic drivers of Sphagnum species distributions is important for predicting the future Climatic drivers of Sphagnum speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 49 publications
2
9
0
3
Order By: Relevance
“…Our results showed that all six species under current climatic scenarios were mainly distributed in North America and Eurasia. The areas with Sphagnum species richness greater than 2 were mainly concentrated in latitudes above 40°N in North America and above 45°N in Europe, which was consistent with the previous studies (Campbell et al, 2021; Gunnarsson, 2005; Oke & Hager, 2017). In addition, Sphagnum ‐dominated peatlands with a small range in the Southern Hemisphere were also realistically represented in this study, including the eastern coastal region of Australia and the southeastern coastal region of South America.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that all six species under current climatic scenarios were mainly distributed in North America and Eurasia. The areas with Sphagnum species richness greater than 2 were mainly concentrated in latitudes above 40°N in North America and above 45°N in Europe, which was consistent with the previous studies (Campbell et al, 2021; Gunnarsson, 2005; Oke & Hager, 2017). In addition, Sphagnum ‐dominated peatlands with a small range in the Southern Hemisphere were also realistically represented in this study, including the eastern coastal region of Australia and the southeastern coastal region of South America.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in the geographic distribution and composition of species driven by climate change are closely linked to the fate of peatland ecosystems. Recent species distribution models (SDMs) for Sphagnum species or Sphagnum bogs have focused on suitable habitat projections on country‐wide and continental‐wide scales (Campbell et al, 2021; Cerrejón et al, 2020; Cong et al, 2020; Oke & Hager, 2017). Oke and Hager (2017) modeled the distribution and expansion of four Sphagnum species in North American peatlands which were tightly influenced by the future climate scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Сфагнові мохи є одними з кріофітів, найбільш залежних від низки чинників, насамперед умов середовища: зволоження, рН, висоти над рівнем моря, типів оселищ, ступеня трансформації рослинного покриву унаслідок антропогенного впливу, в тому числі забруднення і рекреаційного навантаження, змін клімату тощо [20,23,[27][28][29][30]33]. За наявністю певних видів сфагнових мохів на болотах можна судити про ступінь трофності, тобто про абсолютне і відносне багатство болотних екотопів, яке визначається характером відкладень, ґрунтотвірними породами та багатством солей ґрунтових вод, які доступні рослинам [2, 31,33].…”
unclassified
“…Як відомо з літературних даних, сфагни є хорошими індикаторами кислотності ґрунту, показниками зменшення вологості унаслідок зміни доступності води в екосистемах і сезонних коливань температури, що призводить до зменшення видового складу й обмеження поширення сфагнових мохів. Також викопні зразки сфагнових мохів у торфовищах використовують як індикатори минулих кліматичних змін [20,24,29].…”
unclassified
See 1 more Smart Citation